The Public Service And Good Governance In Nigeria’s Fourth Republic: Pitfalls And Opportunities - Ighodalo, Akhakpe (Advances in Social Sciences Research Journal, 2019)
The public service of any nation is conceived as a driver of policies and programmes of government that is aimed at promoting the welfare and well-being of the people and the corporate existence of the State. It is against this back-drop that the return to civil rule in 1999 was seen as an opportunity to stem the tide of socio-economic and political decline in Nigeria. However, more than a decade and half of democratic rule, the citizenry still wallow in abject poverty, insecurity, unemployment, electricity power supply, poor medical care and shelter, corruption, feeble enforcement of transparency and accountability, exclusion of the citizenry from decision making and legitimacy crisis. With the use of political participation theory, the paper observed that the public service is still largely disconnected from the people that it is meant to serve. In most cases it pursues its self-interest rather than the public good. This largely accounts for its assumed abysmal records bad governance in the delivery of democratic dividends across the country. The paper made far-reaching recommendations on how to bring the country out of this unpalatable situation. These include among others: the promotion of core-democratic values, prioritization of professionalism in the public service, capacity building for public servants, promotion of the new public management principles, zero tolerance for corruption, political stability, participatory decision making and promotion of distributive justice. It concluded that regime change also demands change in the attitude, structure and operational dynamics of the public service in order to promote good governance in Nigeria.